2022
DOI: 10.3389/fphar.2022.878726
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Triptolide and the Recent Advances in Treating Non–Small Cell Lung Cancer

Abstract: In recent decades, natural products derived from plants and their derivatives have attracted great interest in the field of disease treatment. Triptolide is a tricyclic diterpene extracted from Tripterygium wilfordii, a traditional Chinese medicine, which has shown excellent therapeutic potential in the fields of immune inflammation and cancer treatment. In this study, 1,106 Web-of-Science-indexed manuscripts and 1,160 Chinese-National-Knowledge-Infrastructure-indexed manuscripts regarding triptolide published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 88 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…TP, an active ingredient in TCM (Wang et al, 2020), plays an inhibitory role in many cancers, such as ovarian cancer (Liu et al, 2019) and thyroid cancer (Wang et al, 2021). Yang et al (2022) found that TP exerted antitumor effects in NSCLC. TP could induce NSCLC cell apoptosis and suppress metastasis (Philips et al, 2020;Reno et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TP, an active ingredient in TCM (Wang et al, 2020), plays an inhibitory role in many cancers, such as ovarian cancer (Liu et al, 2019) and thyroid cancer (Wang et al, 2021). Yang et al (2022) found that TP exerted antitumor effects in NSCLC. TP could induce NSCLC cell apoptosis and suppress metastasis (Philips et al, 2020;Reno et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al. (2022) found that TP exerted anti‐tumor effects in NSCLC. TP could induce NSCLC cell apoptosis and suppress metastasis (Philips et al., 2020; Reno et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to the traditional Chinese drug-disease target protein interaction network and core target bar chart, JUN, AKT1, MAPK1, RELA, IL6, MAPK14, MAPK8, ESR1, FOS, CXCL8 and EGFR might be the core genes that exert anti-lung cancer effect of cortex mori. In tumorigenesis, AKT subtype AKT1 has dual functions, acting both as an oncogene inhibiting apoptosis and an anticancer gene inhibiting invasion and metastasis, which plays a dual role (Yang et al 2018). Lung cancer differentiation, lymph node metastasis, and stage are closely associated with AKT1 expression (Wan et al 2017, Cai et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide (TP), an active diterpenoid extracted from Tripterygium wilfordii, has biological activities such as anti-inflammatory, immunosuppressive, and antitumor activities. TP is a promising antitumor candidate, as it can inhibit tumors in various ways, including inhibition of tumor cell proliferation, immune regulation, inhibition of tumor angiogenesis, and regulation of tumor cell resistance. , TP is effective on common tumor cells, multidrug-resistant cancer cells, and some tumor stem cells . However, with the increasing clinical application of TP, increasing studies and clinical case reports have shown that TP has serious adverse reactions, such as multiple organ toxicity .…”
Section: Introductionmentioning
confidence: 99%